ASESMEN SEBAGAI UPAYA TINDAK LANJUT KEGIATAN IDENTIFIKASI TERHADAP ANAK BERKEBUTUHAN KHUSUS - Dian Puspa Dewi (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
The results of the identification that have been performed on the Children with special needs become the basis for follow-up service delivery. Assessment is a follow-up of identification activities, both of which are a series of inseparable and interrelated processes. Assessment of Children with Special Needs is a systematic or regular and comprehensive process or a whole in exploring further problems to find out what problems, barriers, advantages and individual needs. In the assessment process, an assessment of the three most basic things in Children with Special Needs is the child's deficiency or disability, the surplus or potential of the child and the needs of the child. Assessments are carried out with specific implementation methods and procedures.The results of the identification that have been performed on the Children with special needs become the basis for follow-up service delivery. Assessment is a follow-up of identification activities, both of which are a series of inseparable and interrelated processes. Assessment of Children with Special Needs is a systematic or regular and comprehensive process or a whole in exploring further problems to find out what problems, barriers, advantages and individual needs. In the assessment process, an assessment of the three most basic things in Children with Special Needs is the child's deficiency or disability, the surplus or potential of the child and the needs of the child. Assessments are carried out with specific implementation methods and procedures.